Effectiveness of Personalized Feedback Alone or Combined with Peer Support to Improve Physical Activity in Sedentary Older Malays with Type 2 Diabetes: A Randomized Controlled Trial - Sazlina, Shariff-Ghazali; Browning, Colette Joy; Yasin, Shajahan (Frontiers in Public Health, 2015)
Introduction: Regular physical activity is an important aspect of self management among older people with type 2 diabetes but many remain inactive. Interventions to improve physical activity levels have been studied but few studies have evaluated the effects of personalised feedback or peer support; and there was no study on older people of Asian heritage. Hence, this trial evaluated whether personalised feedback (PF) only or combined with peer support (PS) improves physical activity among older Malays with type 2 diabetes (T2DM) compared to usual care only. Materials and methods: A three arm randomised controlled trial was conducted in a primary healthcare clinic in Malaysia. 69 sedentary Malays aged 60 years and older with T2DM who received usual diabetes care were randomised to PF or PS interventions or as controls for 12 weeks with follow-ups at weeks 24 and 36. Intervention groups performed unsupervised walking activity and received written feedback on physical activity. The PS group also received group and telephone contacts from trained peer mentors. The primary outcome was pedometer steps. Secondary outcomes were self-reported physical activity, cardiovascular risk factors, cardiorespiratory fitness, balance, quality of life and psychosocial wellbeing. Results: 52 (75.4%) completed the 36-week study. The PS group showed greater daily pedometer readings than the PF and controls (p=0.001). The PS group also had greater improvement in weekly duration (p<0.001) and frequency (p<0.001) of moderate intensity physical activity, scores on the Physical Activity Scale for Elderly (p=0.003), six minute walk test (p<0.001) and social support from friends (p=0.032) than PF and control groups. Conclusions: The findings suggest personalised feedback combined with peer support in older Malays with T2DM improved their physical activity levels, cardiorespiratory fitness and support from friends. Trial registration: Current Controlled Trials ISRCTN71447000.